Seasonal population of cardamom thrips (Sciothrips cardamomi (Ramk.) on three cultivar types of cardamom (Elettaria cardamomum Maton) - SELVAN, JASVIR SINGH, M R SUDHARSHAN, M TAMIL (Journal of Spices and Aromatic Crops, 1999)
The seasonal population of cardamom thrips (Sciothrips cardamomi) and its damage to capsules was assessed on three Cllitivar types (Malabar, Vazhukka and Mysore) of cardamom (Elettaria cardamomum) at Saklespur (Karnataka, India) during 1990-92. Thrips population was high during pre-and post-monsoon periods in all the cultivar types. There were significant differences in thrips damage on the capsules in the three cultivar types. There was no significant correlation between abiotic factors and thrips population. The cultivar type Malabar, mainly grown in Karnataka, recorded about 50% less damage than the other cultivar types. Mean thrips damage on capsules during the three years of study in Malabar, Vazhukka and Mysore cultivam types were 28.44%, 57.92% and 62.55%, respectively.